A Study on How Social Media Users in Sub-Saharan Africa are Learning New Health Behaviors - Mayoka Kituyi, Geoffrey; Engotoit, Bernard; Abima, Boniface (My University, 2020)
This study sought to investigate the influence of cognition and locus of control on the health behaviors of social media users so as to mitigate the learning of negative health behaviors by social media users. Four hypotheses were formulated including H1: Cognitive Factors have a positive effect on the Health Behavior of social media users; H2: Cognitive Factors have a positive impact on Internal Locus of Control of social media users; H3: Internal Locus of Control positively affects the Behavioral Intention of social media users; H4: Behavioral Intention positively affects Health Behavior of social media users. Quantitative research methods were used in this study. A sample of 450 social media users was taken from three countries namely; Uganda, Nigeria and Cameroon for data collection using questionnaires. Data were analyzed using descriptive statistics, hierarchical regressions and structural equation modeling techniques. Findings reveal that all the four hypotheses were supported. Given the findings, we recommend that communities implement knowledge enhancement programs such as trainings, education, and sensitization among others. Social media users should be taught on the benefits of using social media for positive health gain. Further, it is recommended that cultural institutions, religious institutions join social media platforms and moderate the learning process. This will enable users to learn new health behaviors that positively affect their health.
Keywords: Cognitive factors; Internal Locus of Control; Social Media; Health Behaviors; Social learning; Cognitive learning